2003
DOI: 10.1002/macp.200350049
|View full text |Cite
|
Sign up to set email alerts
|

New Aromatic tert‐Amines for Application as Photoinitiator Components in Photocurable Dental Materials

Abstract: A new type of aromatic tert‐amine with a bisphenol A (BPA) skeleton has been prepared and applied as a photoinitiator (PI) component for enhancing photosensitivity in formulations of visible light curable dental polymers. Two N,N‐dimethylamino (DMA) groups were incorporated into BPA diglycidyl ether to make 2,2‐bis[4‐(2‐hydroxy‐3‐(p‐N,N‐dimethylaminobenzoyloxy)propyloxy)phenyl]propane (DMABPA). One or two (meth)acryloyl groups were reacted with the hydroxyl groups of DMABPA to obtain the polymerizable, BPA‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…To overcome problems associated with yellowing, aging, toxicity, or incompatibility by the use of simple aromatic or aliphatic amines in conjunction with CQ, some polymeric or macromolecular photoinitiators like aromatic tert-amine with a bisphenol-A skeleton have been recommended 12) . In the same vein, the initiator CQ can be replaced by polymeric radical photoinitiators bearing the photosensitive CQ groups in the side chain 13) .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome problems associated with yellowing, aging, toxicity, or incompatibility by the use of simple aromatic or aliphatic amines in conjunction with CQ, some polymeric or macromolecular photoinitiators like aromatic tert-amine with a bisphenol-A skeleton have been recommended 12) . In the same vein, the initiator CQ can be replaced by polymeric radical photoinitiators bearing the photosensitive CQ groups in the side chain 13) .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the amine free radical, formed after the hydrogen abstraction from amine by activated photosensitizer CQ, starts and guides the polymerization of methacrylate at a high rate. It has been widely reported that the type of amine directly affected the polymerization behavior [49,50]. It has also been reported that the amine systems undergo an acid-base reaction with acidic monomers and this reaction can affect the initiation of the polymerization process [51].…”
Section: Discussionmentioning
confidence: 99%
“…To overcome some of the shortcomings of photoinitiators and the amine co-initiators, studies devoted to the synthesis of polymeric photoinitiators [15][16][17], photoinitiators with covalently bound amines [18,19], and photoinitiators with a polymerizable (meth)acrylate functionality [20][21][22] had been undertaken. The resultant photoinitiators showed significant advantages over the corresponding monomeric photoinitiators, such as low odor and reduced toxicity.…”
Section: Introductionmentioning
confidence: 99%